Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Enhancing microalgal bioremediation and bioproduction with chemical additives: Mechanisms and strategic perspectives - Yongteng Zhao; Shiyu Lin; Qingqing Li; Feiyan Huang; Xiang Wang; Lei Zhang; Xuya Yu; Lei Yu (Algal Research, 2026)

Urban-suburban-rural gradient variations in mortality associated with compound exposure to heat wave and ozone pollution: A case-crossover study using small-area assessment - Kang Ma; Fengman Fang; Xiuya Xing; Yuesheng Lin; Cheng He; Youru Yao; Fei Tong; Jingli Zhu; Huadong Wang; Feiyan Zhang; Ruoxi Li (Journal of Environmental Management, 2026)

Phosphorus-driven enhancement of microalgal growth, lipid biosynthesis, and nutrient removal efficiency in Monoraphidium sp. QLZ-3: Implications for biofuel production and high‑phosphorus wastewater treatment - Shiyu Lin; Jinkun You; Yongteng Zhao; Qingwei Wang; Ying Qi; Feiyan Huang; Xuya Yu; Lei Yu (Algal Research, 2026)

Acetylcysteine combined with budesonide nebulized inhalation for the treatment of pneumonia in children: a meta-analysis - Xiaoxing Wei; Lin Feng; Feiyan Chen (European Journal of Clinical Pharmacology, 2026)

Association of compound exposure to heat wave and ozone pollution with cause-specific cardiopulmonary mortality: A space-time-stratified case-crossover study - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing; Feiyan Zhang; Ruoxi Li (Environmental Research, 2025)

Endophytic Bacteria Enterobacter cloacae PN7 Promotes Biosynthesis and Accumulation of Saponins in Panax notoginseng - Xianjing Lin; Mulan Wang; Feiyan Xie; Yuxi Cheng; Li Yang; Jian Gao; Weiqi Li; Xudong Zhang; Ting Tang (Current Microbiology, 2025)

Insight into simultaneously sludge dewatering and antiviral drugs removal by integrated particle electrodes assisted electrochemical oxidation - Haixiang Yu; Yiyang He; Hong Tao; Haiping Yuan; Feiyan Wu; Rusen Zou; Suyun Xu; Lin Gu (Journal of Environmental Chemical Engineering, 2024)

A self-assembly BiOI/Bi4O5Br2 microcluster and its efficiently visible-light-induced photocatalytic degradation of methylparaben - Kang Deng; Xintong You; Minyi Liu; Yongyi Tan; Yilian Lin; Wei Shu; Feiyan Liu; Shunheng Tu; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Global change progressively increases foliar nitrogen–phosphorus ratios in China's subtropical forests - Yuan Lai; Songbo Tang; Hans Lambers; Peter Hietz; Wenguang Tang; Frank S. Gilliam; Xiankai Lu; Xianzhen Luo; Yutong Lin; Shu Wang; Feiyan Zeng; Qi Wang; et al. (Global Change Biology, 2024)
Globally increased nitrogen (N) to phosphorus (P) ratios (N/P) affect the structure and functioning of terrestrial ecosystems, but few studies have addressed the variation of foliar N/P over time in subtropical forests. Foliar N/P indicates N versus P limitation in terrestrial ecosystems. Quantifying long‐term dynamics of foliar N/P and their potential drivers is crucial for predicting nutrient status and functioning in forest ecosystems under global change. We detected temporal trends of foliar N/P, quantitatively estimated their potential drivers and their interaction between plant types (evergreen vs. deciduous and trees vs. shrubs), using 1811 herbarium specimens of 12 widely distributed species collected during 1920–2010 across China's subtropical forests. We found significant decreases in foliar P concentrations (23.1%) and increases in foliar N/P (21.2%). Foliar N/P increased more in evergreen species (22.9%) than in deciduous species (16.9%). Changes in atmospheric CO 2 concentrations (), atmospheric N deposition and mean annual temperature (MAT) dominantly contributed to the increased foliar N/P of evergreen species, while , MAT, and vapor pressure deficit, to that of deciduous species. Under future Shared Socioeconomic Pathway (SSP) scenarios, increasing MAT and would continuously increase more foliar N/P in deciduous species than in evergreen species, with more 12.9%, 17.7%, and 19.4% versus 6.1%, 7.9%, and 8.9% of magnitudes under the scenarios of SSP1‐2.6, SSP3‐7.0, and SSP5‐8.5, respectively. The results suggest that global change has intensified and will progressively aggravate N–P imbalance, further altering community composition and ecosystem functioning of subtropical forests.

Influence mechanism of tempering for storage quality of dried rice based on the evaluation of physicochemical and sensory characteristics and mitochondrial function and structure - Xudong He; Feiyan Yang; Chunai Liu; Xin Wen; Xueying Zhang; Shuguo Sun; Feijun Luo; Qinlu Lin (Journal of Cereal Science, 2023)

Zirconium tungstate reinforced energetic composites with inhibited thermal expansion and reduced thermal stress - Congmei Lin; Liangfei Bai; Liyuan Wei; Ruqin Liu; Shiliang Huang; Cui Zhang; Xiaoqing Tu; Zhijian Yang; Feiyan Gong; Chengcheng Zeng; Ling Ding; Liping Pan; et al. (Chemical Engineering Journal, 2023)

Combination of highly photovoltaic and highly transparent materials enables record performance semitransparent organic solar cells - Lin Zhao; Xuexiang Huang; Yukai Wang; Sang Young Jeong; Bin Huang; Jiawei Deng; Jiabin Liu; Yujun Cheng; Han Young Woo; Feiyan Wu; Limin Chen; Lie Chen (Chemical Engineering Journal, 2023)

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

QTL identification, fine mapping, and marker development for breeding peanut (Arachis hypogaea L.) resistant to bacterial wilt - Feiyan Qi; Ziqi Sun; Hua Liu; Zheng Zheng; Li Qin; Lei Shi; Qingzheng Chen; Haidong Liu; Xiufang Lin; Lijuan Miao; Mengdi Tian; Xiao Wang; et al. (Theoretical and Applied Genetics, 2022)
Key message A major QTL, qBWA12 , was fine mapped to a 216.68 kb physical region, and A12.4097252 was identified as a useful KASP marker for breeding peanut varieties resistant to bacterial wilt. Abstract Bacterial wilt, caused by Ralstonia solanacearum , is a major disease detrimental to peanut production in China. Breeding disease-resistant peanut varieties is the most economical and effective way to prevent the disease and yield loss. Fine mapping the QTLs for bacterial wilt resistance is critical for the marker-assisted breeding of disease-resistant varieties. A recombinant inbred population comprising 521 lines was used to construct a high-density genetic linkage map and to identify QTLs for bacterial wilt resistance following restriction-site-associated DNA sequencing. The genetic map, which included 5120 SNP markers, covered a length of 3179 cM with an average marker distance of 0.6 cM. Four QTLs for bacterial wilt resistance were mapped on four chromosomes. One major QTL, qBWA12 , with LOD score of 32.8–66.0 and PVE of 31.2–44.8%, was stably detected in all four development stages investigated over the 3 trial years. Additionally, qBWA12 spanned a 2.7 cM region, corresponding to approximately 0.4 Mb and was fine mapped to a 216.7 kb region by applying KASP markers that were polymorphic between the two parents based on whole-genome resequencing data. In a large collection of breeding and germplasm lines, it was proved that KASP marker A12.4097252 can be applied for the marker-assisted breeding to develop peanut varieties resistant to bacterial wilt. Of the 19 candidate genes in the region covered by qBWA12 , nine NBS-LRR genes should be further investigated regarding their potential contribution to the resistance of peanut against bacterial wilt.

Larval Fish Assemblages and Distribution Patterns in the Zhongsha Atoll (Macclesfield Bank, South China Sea) - Delian Huang; Jing Chen; Lei Xu; Xuehui Wang; Jiajia Ning; Yafang Li; Lianggen Wang; Shuangshuang Liu; Zhaojin Lin; Feiyan Du (Frontiers in Marine Science, 2022)
The remote coral reef in the deep sea is one of the most important nursery grounds for many marine fishes in the South China Sea. Diversity studies on larval fishes in this area are few, and the fish information on the coral reefs ecosystem is lacking. In this study, larval fishes were sampled during the summer of 2019 from the Zhongsha Atoll in the South China Sea and identified using DNA barcodes for the first time. Ninety-five larval fish species were recognized, belonging to 37 families and 12 orders based on morphological classification and DNA barcoding identification. The larval fish collected could be assigned to three categories as reef-associated, deep-sea, and pelagic. Most of the species were small fish with low commercial value but would play an essential role in the coral reef ecosystem. Some commercial fishes, including Auxis thazard, Euthynnus affinis, Sarda orientalis, Decapterus macarellus, Lutjanus viridis , and Centropyge vrolikii , were the dominant species higher than 2% total catch. The larval fish assemblage showed distinct spatial differences responding well with the geographical conditions. The most reef-associated fish occurred inside the Atoll, and the abyssal fish presented near the edge. In addition, larval fish spread over from the southwest to northeast may reflect the oceanography effect.

Polyconchoecia commixtus gen. et sp. nov. (Ostracoda: Myodocopa: Halocyprididae) from the South China Sea - Feiyan Du; Peng Xiang; Ruixiang Chen; Lianggen Wang; Yu Wang; Chunguang Wang; Mao Lin (Acta Oceanologica Sinica, 2018)

Piperine potentiates the effects of trans-resveratrol on stress-induced depressive-like behavior: involvement of monoaminergic system and cAMP-dependent pathway - Ying Xu; Chong Zhang; Feiyan Wu; Xiaoxiao Xu; Gang Wang; Mengmeng Lin; Yingcong Yu; Yiran An; Jianchun Pan (Metabolic Brain Disease, 2016)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Enhancement of biodesulfurization by Pseudomonas delafieldii in a ceramic microsparging aeration system - Xing Lin; Huizhou Liu; Feiyan Zhu; Xuetuan Wei; Qiang Li; Mingfang Luo (Biotechnology Letters, 2012)

Identification, isolation and expression analysis of auxin response factor (ARF) genes in Solanum lycopersicum - Jian Wu; Feiyan Wang; Lin Cheng; Fuling Kong; Zhen Peng; Songyu Liu; Xiaolin Yu; Gang Lu (Plant Cell Reports, 2011)